Factors affecting the financial performance of Saudi insurance companies – An Empirical Study on the three largest insurance companies in Saudi Arabia – - Abdulrahman, Najla Ibrahim; Al-Shuraimi, Alaa Nasser (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to identify the impact of independent factors on the financial performance of Saudi insurance companies for the period (2009-2019), and the data was analyzed through the adoption of the statistical tool SPSS, the regression coefficient, and the study concluded the following results: There is an effect of financial raising on the financial performance of measured companies The return on assets, while there is no effect of the financial increase of the financial performance measured by the return on equity. The researchers believe that the reason for this result is that most corporate departments go to invest in the acquisition of new assets, and also there is no relationship between the size of the company and its financial performance, whether it is measured by the return on assets or return on equity. The study recommends that the company’s management, when determining financial leverage, find a degree of balance between the returns that are to be achieved for shareholders with the returns that are to be achieved for the assets, increase the degree of financial leverage for companies to improve financial performance to achieve the returns of shareholders, the need for companies to try to reduce the assumption cost so that it is less than the return on assets to create returns that can be added to equity.
Keywords: financial performance; rate of return on equity; The rate of return on assets